Core requirements of knowledge management implementation, innovation and organizational performance - Al-Hakim, Laith Ali; Hassan, Shahizan (Journal of Business Economics and Management, 2016)
The present study aims to examine the relationship among core requirements of knowledge management implementation, innovation, and organizational performance in the Iraqi mobile telecommunications sector. A questionnaire was conducted on mobile companies based on a proportionate stratified random sampling technique. The results indicated that core requirements of knowledge management implementation had a statistically significant and direct positive effect on innovation. The critical success factors of knowledge management and knowledge management strategies had a statistically significant and direct positive effect on organizational performance. Then the direct relationship of knowledge management processes with organizational performance was positively affected, but it was not statistically significant. The results also indicated that the innovation had a positive and statistically significant effect on organizational performance. More importantly, the results indicate that core requirements of knowledge management implementation had a positive and statistically significant effect on organizational performance through the partial mediating effect of innovation.